Thrombopoietic cytokines in patients with hepatitis C virus-associated immune thrombocytopenia. Issue 1 (2nd January 2017) - Huang, Cih-En; Chen, Yi-Yang; Chang, Jung-Jung; Kuan, Feng-Che; Lee, Kuan-Der; Lu, Chang-Hsien; Lung, Jrhau; Shen, Chien-Heng; Chen, Chih-Cheng
Abstract : Objectives : Complex and multiple mechanisms are involved in the etiology of Hepatitis C virus-associated immune thrombocytopenia (HCV-ITP). Many hematopoietic growth factors affect the thrombopoiesis. The aim of this study was to clarify the interaction of the thrombopoietic factors in patients with HCV-ITP. Methods : We selected 33 patients with HCV-ITP and 17 normal individuals. We compare serum interleukin (IL)-3, IL-6, IL-11, thrombopoietin (Tpo), stem cell factor (SCF), granulocyte-macrophage colony-stimulating factor (GM-CSF), tumour necrosis factor-α (TNFα), and spleen size between these two groups. Results : Our study shows that Tpo, IL-6, and TNFα significantly increased in patients with HCV-ITP compared to the normal population (Tpo:122.577 vs. 40.602; IL-6: 2.175 vs. 0.943; TNFα: 2.460 vs. 1.322). IL-11 was significantly lower in the HCV-ITP group (10.829 vs. 15.042). HCV-ITP patients had a higher spleen index (21.121 vs 13.498, P  = 0.003). According to regression analysis and multiple linear regression analysis, only IL-11 had a significantly positive correlation with platelet count, while TNFα showed a negative correlation. Discussions : Tpo and IL-6 increased in patients with HCV-ITP, suggesting a positive feedback of low platelet count. TNFα-associated immune response is suspected to have an impact on low platelet count. IL-11 is assumed to directly affect thrombopoiesis. Conclusions : This study is the most comprehensive study to evaluate the interaction between platelet count and the important thrombopoetic factors in patients with HCV-ITP. The thrombopoietic factors clearly play an important role in HCV-ITP.